Optimization of traction force microscopy for micron-sized focal adhesions - Stricker, Jonathan; Sabass, Benedikt; Schwarz, Ulrich S. (Journal of physics. Condensed matter, 2010)
To understand how adherent cells regulate traction forces on their surrounding extracellular matrix (ECM), quantitative techniques are needed to measure forces at the cell-ECM interface. Microcontact printing is used to create a substrate of 1 µm diameter circles of ECM ligand to experimentally study the reconstruction of traction stresses at constrained, point-like focal adhesions. Traction reconstruction with point forces (TRPF) and Fourier transform traction cytometry (FTTC) are used to calculate the traction forces and stress field, respectively, at isolated adhesions. We find that the stress field calculated with FTTC peaks near the center of individual adhesions but propagates several microns beyond the adhesion location. We find the optimal set of FTTC parameters that yield the highest stress magnitude, minimizing information lost from over-smoothing and sampling of the displacement or stress field. A positive correlation between the TRPF and FTTC measurements exists, but integrating the FTTC stress field over the adhesion area yields only a small fraction of the force calculated by TRPF. An effective area similar to that defined by the width of the stress distribution measured with FTTC is required to reconcile these measurements. These measurements set bounds on the spatial resolution and precision of FTTC measurements on micron-sized adhesions.